Devon women in public and professional life, 1900-1950 : votes, voices and vocations /: votes, voices and vocations. (2021) - Neville, Julia; Auchterlonie, Mitzi; Auchterlonie, Paul; Roberts, Ann; Turnbull, Helen
No abstract available